Scaling Distributed CI/CD Pipelines for High-Throughput Engineering Teams: Architecture, Optimization, and Developer Experience - Gangadhar Chalapaka, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article comprehensively analyzes strategies and architectures for scaling continuous integration and continuous delivery (CI/CD) pipelines to support high-throughput engineering teams. As organizations grow from dozens to hundreds or thousands of developers, traditional pipeline architectures often become bottlenecks that impede development velocity and increase infrastructure costs. The article examines the evolution from centralized to distributed CI/CD models, highlighting how cloud-native technologies, Kubernetes orchestration, and ephemeral compute resources enable linear scaling capabilities. Through a detailed article on optimization techniques—including multi-level caching strategies, dependency tracking, and dynamic test distribution—the article demonstrates how organizations can maintain consistent performance while controlling costs. Article case studies from microservices environments reveal that properly implemented distributed pipelines can reduce build times while supporting significantly higher deployment frequencies. The article addresses technical implementation and developer experience considerations, providing a roadmap for organizations at different growth stages. The article indicates that the strategic implementation of distributed CI/CD architectures represents a competitive advantage for engineering organizations, enabling them to maintain productivity and innovation cycles even as they scale significantly.
Keywords: Distributed CI/CD Architecture; Pipeline Scalability; Microservices Integration; Build Optimization; Cloud-Native DevOps